The Implementation of Cooperative Script in History Learning in Grade XI at SMA Negeri 3 Kendari - Anwar Hafid (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2026)
This research sought to enhance instructional effectiveness, students’ learning engagement, and history learning outcomes through the application of the Cooperative Script learning model in Class XI.1 at SMA Negeri 3 Kendari. The study employed a Classroom Action Research (CAR) design implemented in two cycles, each consisting of three instructional meetings. The participants included one history teacher and 27 students from Class XI.1. The results demonstrate consistent improvements in all observed aspects. During Cycle I, the level of teaching effectiveness achieved 75%, which increased substantially to 95% in Cycle II, surpassing the predetermined performance standards. Students’ learning activities also showed marked progress, rising from 59.25% in the first cycle to 88.88% in the second cycle, exceeding the target threshold of 85%. In addition, students’ learning outcomes improved from 55.55% in Cycle I to 85.18% in Cycle II, meeting the established criterion of 80%. Based on these findings, it can be concluded that the implementation of the Cooperative Script learning model contributes positively to improving instructional quality, student participation, and learning achievement. By actively engaging students in collaborative learning processes, this model supports the creation of a more interactive and participatory classroom atmosphere. Consequently, the Cooperative Script model may be considered a viable and effective instructional approach for history teaching at the secondary school level.